Expecting the unexpected: nucleic acid-based diagnosis and discovery of emerging viruses. (May 2011) - Barnard, Ross Thomas; Hall, Roy A; Gould, Ernest A
Extrapolation from recent disease history suggests that changes in the global environment, including virus, vector and human behavior, will continue to influence the spectrum of viruses to which humans are exposed. In this article, these environmental changes will be enumerated, and their potential impact on target-focused, nucleic acid-based diagnostic tests will be considered, followed by a presentation of some emerging technological responses.